Entrepreneurial Strategies in New Organizational Populations - Ховард Олдрич (Journal of Economic Sociology, 2010)
Organization-pioneer faces the other difficulties than the organization which just continues the established tradition and follows the other thousand of organizations in the given industry.  Does it mean that this difference in conditions counts for the different strategies for pioneers and followers? The paper of one of classics of ecological approach towards the organization analysis is devoted to the problem of varieties between the organizations that live different life cycle period. The paper is a bright example of the scientific research done within the approach of the “organization ecology”. The establishment of a new organization is a rather risky thing. Despite that there are a lot of institutional restrictions the pioneers have strategies that lead to success at the end.  .